Disruption of Circadian Rhythms by Light During Day and Night - Figueiro, Mariana G. (Curr Sleep Med Rep, 2017)
PURPOSE OF REVIEW: This study aims to discuss possible reasons why research to date has not forged direct links between light at night, acute melatonin suppression or circadian disruption, and risks for disease. RECENT FINDINGS: Data suggest that irregular light–dark patterns or light exposures at the wrong circadian time can lead to circadian disruption and disease risks. However, there remains an urgent need to: (1) specify light stimulus in terms of circadian rather than visual response; (2) when translating research from animals to humans, consider species-specific spectral and absolute sensitivities to light; (3) relate the characteristics of photometric measurement of light at night to the operational characteristics of the circadian system; and (4) examine how humans may be experiencing too little daytime light, not just too much light at night. SUMMARY: To understand the health effects of light-induced circadian disruption, we need to measure and control light stimulus during the day and at night.